2005
DOI: 10.1016/j.jsgi.2005.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Binding Protein in Endometriosis

Abstract: The decreased level of DBPE in the PF but not in PL of women with untreated endometriosis suggests that this molecule may be relevant in the pathogenesis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 33 publications
1
21
0
2
Order By: Relevance
“…A study using proteomic technologies for VDBP analysis demonstrated its presence in the PF of women with endometriosis, whereas one vitamin D binding protein (DBP) isoform (DBPE) was expressed to a lower degree in the PF of women with untreated endometriosis compared to the control group. 104 However, another study found no difference between serum and peritoneal fluid levels of VDBP of women with endometriosis compared to the control group. 105 VDBP levels were also evaluated in urine samples of women with endometriosis and found to be significantly higher in women with endometriosis, albeit the sensitivity (58%) and specificity (76%) of this method limits its diagnostic value.…”
Section: Vitamin D and Endometriosismentioning
confidence: 96%
“…A study using proteomic technologies for VDBP analysis demonstrated its presence in the PF of women with endometriosis, whereas one vitamin D binding protein (DBP) isoform (DBPE) was expressed to a lower degree in the PF of women with untreated endometriosis compared to the control group. 104 However, another study found no difference between serum and peritoneal fluid levels of VDBP of women with endometriosis compared to the control group. 105 VDBP levels were also evaluated in urine samples of women with endometriosis and found to be significantly higher in women with endometriosis, albeit the sensitivity (58%) and specificity (76%) of this method limits its diagnostic value.…”
Section: Vitamin D and Endometriosismentioning
confidence: 96%
“…The presence of DBP in ascitic fluid may be explained by the hydrostatic pressure gradient between plasma and the peritoneal cavity [47]. The determination of DBP in peritoneal fluid could be useful to monitor vitamin D deficiency in peritoneal dialysis patients.…”
Section: Vitamin D Binding Protein In Ascitic Fluidmentioning
confidence: 99%
“…Borkowski J. et al [89] сравнивали общие концентрации ВДСП в сыворотке и в перитонеальной жидкости у женщин с эндометриозом и без него и не об-наружили различий. В другом исследовании, посвящен-ном ВДСП, сообщалось, что одна изоформа ВДСП встре-чалась значительно реже в перитонеальной жидкости, но не в плазме женщин с эндометриозом по сравнению со здоровыми женщинами [90].…”
Section: синдром поликистозных яичников (спя)unclassified